Beyond paradigms in Organization Studies: the Circle of Epistemic Matrices - Ana Paula Paes de Paula (Cadernos EBAPE.BR)
Abstract In this article, I present a sketch of a new proposition to guide organizational studies: the Cicle of Epistemic Matrices. Inspired by Thomas Kuhn and based on the thesis of paradigms' incommensurability, Gibson Burrell and Gareth Morgan drew the diagram of sociological paradigms, but its inclusion in the academy has encouraged a paradigms war. The Circle of Epistemic Matrices also provides an outline for the guidance of organizational studies, but it is based on Habermas and defends the thesis of cognitive incompleteness, suggesting that the sociological and organizational knowledge grows according to the thesis of epistemic reconstructions. To accomplish these propositions and elaborations, I present the debate about the paradigms' war in literature and I question the adequacy of sociological paradigms of Gibson Burrell and Gareth Morgan to organizational studies, with the issue of the influence that it suffered from Kuhnian paradigms and logic. In the following sections, there is an exhibition of alternative proposition - the of Circle of Epistemic Matrices - and, also, I support the thesis of cognitive incompleteness and the thesis of epistemic reconstructions in order to bring a new theory of knowledge development to the area. Finally, I present the findings and thoughts for future research.